Partisipasi Masyarakat dalam Pengembangan Perpustakaan Perguruan Tinggi: Kajian Implementasi UU RI No. 25 Tahun 2009 Tentang Pelayanan Publik di Perpustakaan PTKIN se-Propinsi Jawa Timur - Mohammad Mansyur; Hary Supriyatno (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2019)
This study aims to determine the form of collaboration between the library and the community while measuring the level of utilization and participation of the community in the development of libraries. The community in this study can be Government Agencies, Corporations / Companies and Non-Governmental Organizations. There are five interrelated elements in the library management concept that can be used as objects of cooperation in improving services, namely collections, Human Resources, users, services, and infrastructure. During this time the main constraints of the library are operational costs in the procurement and development of both collections, human resources, and infrastructure. In library science, procuring collections can be done by buying, gifts, donations, and exchanges. Perhaps this is the gap that can be used by librarians in procuring and developing collections in the library. Librarians can collaborate with the community in an effort to increase collections, HR and services without having to be constrained by the lack of available funds. This is also the implementation of RI Law No. 25 of 2009 concerning Public Services Chapter VI Article 39 paragraph 2 which states that